Estimation of Additive and Dominance Effects in an Acacia crassicarpa Multi-Environment Progeny Trial Using Genomic Pedigree Reconstruction - Gustavo S Martins; Muhammad Yuliarto; Wong Ching Yong; Tisha Melia; Maggie V Maretha; Mukesh Sharma; Nathan Lakey; Jared Ordway; Juan José Acosta; Gary Hodge (Forest Science, 2024)
Acacia crassicarpa is an important tree species in Southeast Asia, where hundreds of thousands of hectares of planted forests are supported by advancements in silviculture and genetic improvement. Although possible, controlled pollination is impractical for advancing breeding populations, requiring an unreasonable effort to produce more than a few crosses per year. For this reason, breeding populations often are bred by open pollination. This study used large-scale pedigree reconstruction in multi-environment trials to assess full-sib families to model the genetics of the quantitative traits survival, straightness, height, diameter at breast height, tree volume, mean annual increment (MAI), and basic density. The traits were predominantly controlled by additive effects, with heritabilities between 0.09 for survival and 0.45 for basic density. The genetic correlation across sites was high for all traits, showing the low impact of genotype-by-environment interaction. The trait-trait correlation showed that straightness was independent of any other traits, survival was only correlated with MAI, and growth traits were highly correlated among themselves. Basic density was positively correlated with growth traits and MAI. Study Implications: Parentage analysis using an informative single nucleotide polymorphism panel was used to reconstruct pedigree and allow a full-sib family model to estimate additive and dominance effects and genetic correlations across sites and among important traits in an open-pollinated population. The genetic control of all traits assessed in this study was mainly additive. In this scenario, the recommended breeding strategy is forward selection of outstanding progeny for advanced generation breeding and backward selection of outstanding parents to produce seed for deployment via family forestry. Full-sib families can be identified by pedigree reconstruction at a seedling stage, followed by tissue culture multiplication, rooted cutting propagation, and plantation establishment.